STABILITY OF STELLAR SYSTEMS ORBITING SGR A* - Kahil, Magd E. (Одеські астрономічні публікації, 2016)
Path equations of different orbiting objects in the presence of very strong gravitational fields are essential to examine the impact of its gravitational effect on the stability of each system. Implementing an analogous method, used to examine the stability of planetary systems by solving the geodesic deviation equations to obtain a finite value of the magnitude of its corresponding deviation vectors. Thus, in order to know whether a system is stable or not, the solution of corresponding deviation equations may give an indication about the status of the stability for orbiting systems.Accordingly, two questions must be addressed based on the status of stability of stellar objects orbiting super-massive black holes in the galactic center. 1. Would the deviation equations play the same relevant role of orbiting planetary systems for massive spinning objects such as neutron stars or black holes? 2. What type of field theory which describes such a strong gravitational field?